2020
DOI: 10.3389/fvets.2020.00535
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Allogrooming Through a Dynamic Social Network Approach: An Example in a Group of Dairy Cows

Abstract: For gregarious species such as domestic cattle, the social environment is a very important determinant of their welfare and fitness. Understanding the complexity of cows' relationships can assist the development of management practices that are more integrated with the cows' social behavioral processes. The two aims of this study were: (1) to determine the dynamics of affiliative relationships, as indicated by allogrooming, by means of stochastic actor-oriented modeling, in dairy cows during early lactation; (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 72 publications
(106 reference statements)
1
20
0
Order By: Relevance
“…Allogrooming and self-grooming are rare but conspicuous behaviours which can be easily recognised. Allogrooming in dairy cows was reliably detected by multiple observers during live observations (Kendall's W = 0.96 for 3 observers, Westerath et al, 2009a; ICC = 0.87 de Freslon et al, 2020). A similar agreement has been reported for self-grooming and brush use in calves (Zobel et al, 2017;Horvath and Miller-Cushon, 2019) and steers (Toaff-Rosenstein et al, 2016).…”
Section: Allogrooming Self-grooming and Brushingsupporting
confidence: 55%
“…Allogrooming and self-grooming are rare but conspicuous behaviours which can be easily recognised. Allogrooming in dairy cows was reliably detected by multiple observers during live observations (Kendall's W = 0.96 for 3 observers, Westerath et al, 2009a; ICC = 0.87 de Freslon et al, 2020). A similar agreement has been reported for self-grooming and brush use in calves (Zobel et al, 2017;Horvath and Miller-Cushon, 2019) and steers (Toaff-Rosenstein et al, 2016).…”
Section: Allogrooming Self-grooming and Brushingsupporting
confidence: 55%
“…Researchers have demonstrated that inter-individual variation in sociality is an individual trait in dairy cows ( 28 ) influenced by dominance status and personality traits. This may affect an individual's ability to gain resources, such as cubicles, impacting their proximity interactions in the non-feeding zone ( 17 , 21 ), as also speculated by ( 14 ), although we cannot distinguish between these potential factors in this study.…”
Section: Discussionmentioning
confidence: 91%
“…Individual attributes are thought to be important in disease transmission ( 7 ), as cows participate in contact behaviors based on age and sex. Dairy cows may groom conspecifics based on familiarity and dominance ( 21 ), although affiliative and agonistic interaction networks may not be correlated ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples abound of animals showing prosocial behavior -improving another individual's welfareand enduring relationships (partnerships, bonds, sometimes called friendships; see Massen et al 2010, Seyfarth andCheney 2012). Among them are primates like chimpanzees and baboons, horses, dolphins, elephants, hyenas (for references, see Seyfarth and Cheney 2012), cows (e.g., de Freslon et al 2020), rodents such as voles (Young and Wang 2004) and rats (Ben-Ami Bartal et al 2014), birds like parrots (Brucks and von Bayern 2020), and fish (Soares et al 2012). Evidence of prosocial behavior and enduring relationships extends to plants and bacteria, as indicated by studies on mutualisms between plants and mycorrhizal fungi (Kummel and Salant 2006, Kiers et al 2011, Fellbaum et al 2012) and between legumes and rhizobia Taylor 2002, West et al 2002).…”
Section: Enduring Relationships Among Animals Plants and Bacteriamentioning
confidence: 99%